Effect of Breeding Activity on the Microflora of the External Genitalia and in the Semen of Stallions, and the Relationship Between Micro‐organisms on the Skin and on the External Genitalia. Issue 6 (15th September 2014) - Guimarães, T; Miranda, C; Pinto, M; Silva, E; Damásio, L; Costa, AL; Correia, MJ; Duarte, JC; Cosinha, C; Lopes, G; Thompson, G; Rocha, A
Contents A possible role of breeding activities in the composition of the microbial population in stallions' external genitalia (EG) and the relationship between micro‐organisms colonizing the skin of the abdomen and the ones colonizing the EG have not been studied. In experiment 1, EG microbiological samples were collected from 41 stallions used for both natural cover and semen collection (BST) and from 18 non‐breeding stallions (NBST). A higher (p < 0.05) frequency of isolation of potentially pathogenic species was found for BST. Age did not influence number of micro‐organism species isolated both in BST and NBST. In experiment 2, the microbial content of the EG and semen was compared in 23 BST. Most micro‐organisms isolated from the EG were present in semen, albeit with a numerically lower prevalence. In 7 stallions, six microbial species isolated from semen were absent from the EG cultures, suggesting contamination by the operator. In experiment 3, a numerically higher number of micro‐organism species was isolated from the EG of 31 stallions, than from their skin of the ventral abdomen in contact with the penis or from the skin of the thorax. With the sole exception of Escherichia coli, potentially pathogenic bacteria were only isolated from the EG but not from the skin. Results suggest that breeding activity increased the number of species colonizing the EG; most species isolated from the EG were also found in semen even if with a lower frequency, and additional semen contamination seemed to occur during its manipulation. Many micro‐organism species of the skin were also isolated from the penis, but independently of being or not in contact with the penis, skin did not seem to provide an adequate environment for the growth of potentially pathogenic bacteria that were isolated from EG, with the sole exception for E. coli.